STRATEGY FOR FORMULATION OF THE COMPANY'S VISION, MISSION, OBJECTIVES AND STRATEGY (A STRATEGIC MANAGEMENT STUDY FOR BUSINESS SUSTAINABILITY) - Nurhayati Azis; Ackhriansyah Ahmad Gani; Indriani; Syauqiah Auliah Syam (Journal Informatic, Education and Management (JIEM), 2026)
Strategic management has become the primary foundation for organizations in facing the dynamics of a volatile, uncertain, complex, and ambiguous (VUCA) business environment. Amid rapid technological change , shifting consumer preferences , and global competition , companies cannot rely solely on traditional management practices . One of the most critical foundations in strategic management is the formulation of a company's vision , mission , goals, and strategy . These four elements form an interrelated planning hierarchy : the vision provides a picture of the ideal future , the mission explains the reason for the organization's existence , goals set measurable targets , and strategies provide action plans . This article aims to comprehensively examine the strategies for formulating these four elements based on classical to contemporary strategic management literature . The method used is a literature study with a descriptive-qualitative approach , analysing various textbooks , indexed international journals , and teaching modules . The results of the study indicate that the formulation of a vision must involve elements of core ideology ( core values ​​and core goals ) and an envisioned future (BHAG and vivid description). The mission must be formulated with answers Drucker's fundamental questions about business , customers , and added value . Objectives should follow SMART criteria and be developed at three levels : corporate , business, and functional . Strategies are formulated through SWOT analysis and a matrix of strategic alternatives (SO, WO , ST, WT). Systematic integration of these four elements has been shown to enhance sustainable competitive advantage . This article also presents a practical framework , company case examples , and implementation recommendations for managers and academics.